Meckel’s Diverticulitis as a Cause of an Acute Abdomen in the Second Trimester of Pregnancy: Laparoscopic Management - Ivilina Pandeva; Sumit Kumar; Atif Alvi; Hema Nosib (Case Reports in Obstetrics and Gynecology)
Introduction. Meckel’s diverticulitis is an extremely rare cause of an acute abdomen in pregnancy. Its clinical presentation tends to be rather unusual and therefore commonly delaying diagnosis. The surgical method of exploration can be either by laparoscopy or through an open incision. Case Report. We report a case of a 34-year-old, P1 with previous Caesarean section, who presented at 20 weeks with worsening right-sided abdominal pain, distention, and peritonism. Ultrasound scan showed an area of a possibly thickened loop of bowel inconsistent with an appendicitis. The findings at laparoscopy were purulent fluid in the pelvis, a congested appendix, and inflamed Meckel’s diverticulum. An appendectomy and excision of the diverticulum was performed using stapler technique. Discussion. Meckel’s diverticulitis in pregnancy can have nonspecific presentation and poses difficulties for preoperative diagnosis. Delay in diagnosis and management poses significant maternal and fetal risks. The use of laparoscopy if the gestational age and uterine size permit its use allows a thorough exploration of the abdominal cavity and management of rarer and unexpected pathology. Laparoscopic management of acute abdomen in the midtrimester of pregnancy has been found to be safe and effective.